Proposed Temporary Waqf Model For Family Waqf Implementation In Malaysia - Muhamad Firdaus Ab Rahman; Hussein ‘Azeemi Abdullah Thaidi; Farhana Mohamad Suhaimi; Siti Farahiyah Ab Rahim (Emerald Publishing Limited, 2024)
Volume 15, Issue 1, Pages 56 - 78